ANALISIS YURIDIS PERTIMBANGAN HAKIM DALAM PERKARA TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK (STUDI PUTUSAN NOMOR 2627/PID.Sus/2019/PN.Sby) - Nazhif Aldimas Syahreza; Maria Novita Apriyani (Halu Oleo University, 2025)
This study aims to analyse the Legal Considerations of Judges in Cases of Sexual Violence Against Children (Study of Decision Number 2627/Pid.Sus/2019/PN.Sby). In compiling this journal, the author conducted normative research. Normative research is conducted by approaching problems through laws and regulations, approaching problems conceptually, and approaching problems through cases. The author analysed to see how judges considered aggravating or mitigating criminal penalties that did not follow the prosecutor's demands and laws and regulations. The results of the study show that in case No. 2627/Pid.Sus/2019/PN Sby, the judge considered elements of aggravation and reduction of criminal penalties by considering legal and non-legal aspects, such as the condition of the defendant, trial facts, and laws and regulations. The judge also used his prerogative in handing down a criminal sentence against the defendant MEMET in the form of a 12-year prison sentence, a fine of Rp100,000,000 with a subsidiary of 3 months in prison, and an additional sentence of chemical castration for 3 years, as demanded by the public prosecutor in the case of sexual violence against children. This decision reflects law enforcement efforts that consider substantive justice and protection of victims.